Effect of Extrusion on the Microstructure and Tribological Behavior of Copper–Tin Composites Containing MoS2. Issue 6 (1st November 2016) - Senthil Kumar, P.; Manisekar, K.; Vettivel, S. C.
ABSTRACT: This article deals with the effect of extrusion on the microstructures and tribological properties of powder metallurgy–fabricated copper–tin composites containing MoS2 by optical microscopy, scanning electron microscopy (SEM), and tribotesting. The extrusion decreases the number of pores and increases the density and hardness and thus improves the tribological properties of the composites. Results demonstrated that abrasion is the dominant wear mechanism in all extruded composites, whereas a combination of adhesion and delamination appears to be the governing mechanism for prepared composites. The developed hot-extruded composites exhibited lower coefficient of friction and wear rates compared to prepared composites. Design Expert software was used to develop contour map.